Development and Validation of the Pediatric Sleep Practices Questionnaire: A Self-Report Measure for Youth Ages 8–17 Years. Issue 1 (2nd January 2021) - Meltzer, Lisa J.; Forrest, Christopher B.; de la Motte, Anna; Mindell, Jodi A.; Bevans, Katherine B.
ABSTRACT: Objective : To develop and evaluate the validity of a self-report measure of sleep practices for youth 8–17 years. Methods : Following recommended guidelines for the development of patient reported outcomes (PROs), sleep practice concepts were identified through expert (n = 8) and child (n = 28) concept elicitation interviews and a systematic literature review. Items were developed based on these concepts and tested in cognitive interviews with children (n = 32). Psychometric analyses were applied to item response data collected from a diverse sample of youth 8–17 years (n = 307). Construct validity was evaluated through tests of associations between sleep practices and sleep disturbance and sleep-related impairment. Finally, clinical validity of the tool was assessed by comparing scores of youth with and without a parent-identified sleep problem. Results : The final Pediatric Sleep Practices Questionnaire (PSPQ) included 15 items that were used to identify 5 sleep practices: sleep timing, sleep routines and consistency, technology use before bedtime, sleep environment, and the need for parental presence to fall asleep. A confirmatory factor analysis supported the hypothesized structure (all factor loadings ≥ 0.72) and PSPQ indices were significantly associated with self-reported sleep disturbances and sleep-related impairment. Finally, children with parent-reported sleep problems had shorter sleep opportunity, later bedtimes, greater need for parental presence, poorer bedtime routines, and more technology use than children without parent-reported sleep problems. Conclusions : The PSPQ was developed using best-practice PRO development methodology. The PSPQ can be used in clinical settings and for research assessment to capture modifiable sleep practices that may promote or interfere with healthy sleep.